2015
DOI: 10.1016/j.jvsv.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Durability of treatment effect with polidocanol endovenous microfoam on varicose vein symptoms and appearance (VANISH-2)

Abstract: Treatment with polidocanol endovenous microfoam 1% led to durable, clinically meaningful, and ongoing improvements at 1 year in varicose vein symptoms and appearance. Serious adverse events were those expected during long-term follow-up of the population of patients studied and were unrelated to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…17 The U.S. FDA has indicated that PROMs on symptoms and appearance is of greater importance that duplex ultrasound in the assessment of success in the treatment of varicose veins. 16 In the end, the potential of PROMs can be extended to optimize clinical effectiveness in deciding which patients should be offered a follow-up visit and which not. Patients with persistent problems or complications should be the only ones offered clinical follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…17 The U.S. FDA has indicated that PROMs on symptoms and appearance is of greater importance that duplex ultrasound in the assessment of success in the treatment of varicose veins. 16 In the end, the potential of PROMs can be extended to optimize clinical effectiveness in deciding which patients should be offered a follow-up visit and which not. Patients with persistent problems or complications should be the only ones offered clinical follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…One-year efficacy data showed that although the product demonstrates sustained efficacy in terms of PROs, there was a reduction in sustained ultrasound response to treatment as measured by elimination of reflux through SFJ or complete occlusion of target incompetent vein. 54 Seventy-three per cent of patients demonstrated a sustained ultrasound response at one year compared to 89% at week 8.…”
Section: Clinical Trialsmentioning
confidence: 92%
“…Efficacy: BTGs have demonstrated that the product is efficacious and this is confirmed in one-year follow-up. 54 However, POL has previously been shown to be efficacious. BTG has effectively reconfirmed the established benefits of POL for varicose vein management.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…There is also a 1% polidocanol formulation named Varithena (BTG International, West Conshohocken, PA, USA) [ 63 ]. Varithena is FDA approved (since 2013) for the closure of visible varicose veins, as well as truncal incompetent veins.…”
Section: Non-thermal Techniquesmentioning
confidence: 99%